Sistem Informasi Harga Pasar Toba Berbasis Webiste dan Mobile - Siregar, Alfredo Benaya; Hutapea, Oppir Leonardo; Muliyana, Ana; Nainggolan, Samuel Leonardo; Br Tarigan, Gishella Putri Vehuliza; Gurning, Yosia Yehezkiel; Lumbantoruan, Wahyudi Gamaliel; Simangunsong, Restu Glorya (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study develops a digital system for monitoring and providing price information in traditional markets in Toba Regency. The project addresses the lack of price transparency and difficulties faced by both merchants and consumers in accessing accurate market price data. The system is built using the Waterfall methodology and implements a website and mobile application using Flutter and Golang. Key features include price data input by market managers, administrative supervision by the Department of Cooperatives and Trade (Koperindag), and real-time public access to market prices. The application supports authentication, price management, and category control, and allows the export of reports. Testing was conducted using blackbox and performance methods. Results show that the system improves efficiency, transparency, and accessibility of market price data, supporting digital transformation in local trade.